Predictors of adverse cardiovascular events in patients with coronary artery disease after percutaneous coronary intervention - A. V. Svarovskaya; E. A. Kuzheleva; A. A. Arzhanik; V. A. Fediunina; V. A. Aleksandrenko; A. D. Starchenko; A. A. Garganeeva (Российский кардиологический журнал)
Aim. To identify predictors of major adverse cardiovascular events (MACE) in patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI).Material and methods. This prospective single-center study included 225 patients with stable CAD requiring drug-eluting stent implantation. The average follow-up period for patients was 14,5 (6;23) months. Levels of glycated hemoglobin (HbA1c), insulin, tumor necrosis factor (TNF)-α, interleukin-6 (IL-6), interleukin-10 (IL-10), endothelin-1 (ET-1) and the serum lipid profile were evaluated. Insulin resistance was assessed by the HOMA-IR index. The patients were divided into 2 groups: group 1 (n=98) — patients with MACE, group 2 (n=127) — patients without MACE over the follow-up period.Results. During the follow-up period, MACE were recorded in 43,5% of patients, of which: fatal outcome in 3 (3,1%) patients, acute coronary syndrome (ACS) — 14 (14,3%), decompensated heart failure (HF) — 8 (8,2%), non-fatal myocardial infarc tion (MI) — 4 (4,1%), stroke — 3 (3,1%), in-stent restenosis — 18 (18,4%), target vessel revascularization due to progression of atherosclerosis — 25 (25,4%), lifethreatening arrhythmias — 18 (18,4%), implantation of a cardiac resynchronization therapy defibrillator — 5 (5%). To determine critical levels for quantitative predictors, ROC curves were created with threshold values that increase the likelihood of MACE.Conclusion. As a result of the study, we found that the waist-to-hip ratio >1,0495, the HOMA-IR index >3,13 and the endothelin-1 >0,75 mmol/L are independent predictors of unfavorable prognosis in patients with CAD after PCI.